Perdamaian dan Hak Asasi Manusia di Sri Lanka: Perjuangan Masyarakat Marjinal dalam Mengadvokasi Keadilan - Scott Robert Hearnden (Badan Strategi Kebijakan Hukum, 2024)
Peace and human rights serve as a check on the dominant or majoritarian culture. An absence of human rights is conducive to weak democratic forms, unequal social and political relations, marginalisation, oppression and, in some cases, criminalisation of communities. Such a scenario can be found in Sri Lanka. This paper expands upon a principal research project which found that the marginalisation of participants arose from aspects of their particular identities, including diverse sexualities and genders, races, ethnicities, religions and youth. The principal research was informed by intersectionality, social interactionism, interviews and interpretative phenomenological analysis. This paper was composed out of the research results and was further structured by literature review. People's marginalisation, oppression and exclusion are related directly to the absence of peace and human rights manifested through injustices and structural barriers that frustrated social and political participation.